An experimental and numerical study on turbulent combustion of hydrogen-rich coal gases in a generated non-premixed burner. (15th April 2017) - Ilbas, Mustafa; Karyeyen, Serhat
Abstract: This paper deals with combustion behaviours of the hydrogen-rich coal gases in a generated non-premixed burner integrated with a combustor. In the experimental part of this study, temperature and emission values have been determined on different axial and radial positions by thermocouples and a flue gas analyzer in the combustion chamber. The model validation has been done and the effect of the turbulence models on predictions has been examined in the numerical part of the present study. All experiments and predictions have been performed for thermal power of 10 kW and equivalance ratio of ϕ  = 0.83. The numerical modelling of turbulent diffusion flames has been performed by a CFD code. The standard k-ε model of turbulent flow, the PDF/Mixture Fraction combustion model and P-1 radiation model have been used in the modellings. It can be said that the temperature predictions are in good agreement with the temperature measurements under the same conditions. It may be additionally concluded that the velocity distributions affect the movement of the combustion products considerably. According to the measurements, the results show that the maximum temperature levels emerged in the flame zone for all cases. The maximum flame temperatures of the coke oven gas, town gas-I, town gas-II and water gas have been measured as 1470 K, 1406 K, 1376 K and 1345 K, respectively. In addition to the temperature measurements, NOX, CO2 and CO emissions have been determined in the present study. According to the measurements, it is observed that there is a proportional correlation between the temperature and NOx distributions; higher the temperature, higher the NOx emission. From these measurements, it is revealed that the maximum NOX value measured as of 93 ppm in the flame zone of the town gas-II due to molecular nitrogen in the fuel as well as that in air. It is also concluded that molecular CO2 and CO in the fuels lead to excess CO2 and CO formations.